TRANSLATION OF EUPHEMISM, SYMBOLISM, AND PARADOX EXPRESSIONS FOUND IN THE BIBLE - Adelia Hotryanti; Evert H. Hilman (IKIP Siliwangi, 2024)
The purpose of this study is to analyze selected figurative language items, specifically euphemism, symbolism, and paradox expressions, found in the Bible using the techniques of translation, by Newmark. This study utilizes a descriptive qualitative method with purposive sampling technique. The Data in this research is The Bible in two different translated versions, the International New Version and the Indonesian Version. In this study there are 6 types of translation methods and 2 types of translation procedures employed to translate the bible. There are 4 sentences in Transposition Procedure, 3 sentences in Communicative Translation, 2 sentences in Free Translation, 1 Sentence in Faithful Translation, 1 sentence in Literal Translation, 1 Sentence in Functional Equivalent procedure, and 1 Sentence in Semantic Translation.